Silica Quartz Characteristics from Local Silica Sand on Compressive Strength of Mortar - . Mansyur; M. Tumpu; Parea R. Rangan (Salehan Institute of Higher Education, 2024)
Many minerals, including quartz sand, granite, and feldspar, contain silica (SiO2), a substance that performs the same function as quartz. Silicate (SiO2), the primary mineral found in silica sand, can be added to concrete mixtures to boost strength. This means that silica sand can be employed as a cementitious component in concrete because it is believed to have pozzolanic and amorphous qualities. This study is part of a series that tries to use silica sand from an area in Indonesia. The purpose of this research was to manufacture and describe quartz silica (QS) from Kolaka silica sand, which was acquired from Southeast Sulawesi province in eastern Indonesia. In order to improve the characteristics of mortar mixtures that use composite Portland cement as a binder, it is advised to combine the X-ray diffraction process with an evaluation of the impact of addition (QS) on their physical and mechanical properties (volume weight and compressive strength). Laboratory experimentation is being conducted here. Water, cement, and silica sand are used to make mortar specimens. Red and white silica sand is the type of silica utilized. The specimens were created with a 50 mm diameter and a 100 mm height. Tests on mortar's compressive strength were performed after 7, 14, and 28 days. The study's findings indicated that the amounts of quartz formed in red and white silica sand were 45.05% and 91.87%, respectively. The volume weight that results is approximately 2.78 gr/cm3. Red silica sand was tested for compressive strength at ages 7, 14, and 28 days, and the findings were 20.73, 23.32, and 24.61 MPa, respectively. White silica sand has compressive strengths of 21.83, 24.67, and 26.52 MPa. We are aware of no prior studies examining the use of crystalline silica from Kolaka silica sand to enhance the mechanical qualities of cement mortar. Doi: 10.28991/CEJ-2024-010-08-010 Full Text: PDF